1983
DOI: 10.1128/aem.46.5.1093-1096.1983
|View full text |Cite
|
Sign up to set email alerts
|

Binding Characteristics of Lectins Involved in the Trapping of Nematodes by Fungi

Abstract: Seventeen saccharides were tested for their ability to bind to the trap lectins of three species of nematode-trapping fungi and prevent nematode capture. The lectin of Arthrobotrys conoides was found to be inhibited by α- d -glucose/ d -mannose and similar saccharides. The lectins of Monacrosporium eudermatum and Monacrosporium rutgeriensis were inhibited by α- l -fuco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results reported here complement those of others (5,7), who observed that nematode capture is inhibited by various sugars and suggested that entrapment is mediated by interaction of a lectin on the surface of the fungus trap and a specific sugar on the nematode cuticle. The presence of GalNAc residues on the nematode cuticle has already been demonstrated (5, 9).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The results reported here complement those of others (5,7), who observed that nematode capture is inhibited by various sugars and suggested that entrapment is mediated by interaction of a lectin on the surface of the fungus trap and a specific sugar on the nematode cuticle. The presence of GalNAc residues on the nematode cuticle has already been demonstrated (5, 9).…”
supporting
confidence: 90%
“…However, all evidence for the existence of fungal protein that binds sugar is indirect. It consists solely of demonstrations that exposure of hyphal traps to specific sugars interferes with nematode capture (5,7). It was desirable, therefore, to attempt direct isolation from the fungus of a protein able to bind specific cuticular sugar molecules and influence the process of nematode capture.…”
mentioning
confidence: 99%
“…The traps of A. oligospora that are challenged by GalNAc ( N -acetylgalactosamine) lost the ability to capture nematodes [ 35 ]. Other monosaccharaides such as glucose and mannose can also inhibit the capacity of the trapping-fungi to recognize nematodes [ 36 ]. However, the knocked out lectin-coding gene in A. oligospora did not affect the trapping ability or vegetative growth [ 37 ].…”
Section: Nematophagous Fungimentioning
confidence: 99%
“…2-Deoxy-D-glucose does not occur in nature and its presence has not been demonstrated on nematode cuticles (Jansson, 1987). This carbohydrate has been shown to inhibit cell wall synthesis in the yeast Saccharomyces cerevisiae (Biely et al 1971) as well as inhibiting nematode capture by A. oligospora, Monacrosporium rutgeriensis (Rosenzweig & Ackroyd, 1983) and Dactylaria Candida (Nordbring-Hertz, Friman & Mattiasson, 1982). The inhibitory effect may therefore be due to interference with the production of a penetration hypha rather than the inhibition of a recognition system.…”
Section: Discussionmentioning
confidence: 99%